2020
DOI: 10.1093/sleep/zsaa249
|View full text |Cite
|
Sign up to set email alerts
|

Chronic apnea during REM sleep increases arterial pressure and sympathetic modulation in rats

Abstract: Study objectives Obstructive sleep apnea can induce hypertension. Apneas in REM may be particularly problematic: they are independently associated with hypertension. We examined the role of sleep stage and awakening on acute cardiovascular responses to apnea. Also, we measured cardiovascular and sympathetic changes induced by chronic sleep apnea in REM sleep. Methods We used rats with tracheal balloons and electroencephalogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The authors found that 15 days of experimentally-induced obstructive apneas in REM sleep in rats caused not only REM sleep fragmentation and decreased REM sleep time, but also increased both wake BP and sleep sympathetic modulation as measured from heart rate variability. In addition, the changes in sympathetic modulation and arterial pressure were mostly due to arousals during REM sleep [14]. These data suggest that OSA may alter the physiological response to arousals by exacerbating BP increases, possibly as a result of impaired baroreflex and/or elevated sympathetic activity.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors found that 15 days of experimentally-induced obstructive apneas in REM sleep in rats caused not only REM sleep fragmentation and decreased REM sleep time, but also increased both wake BP and sleep sympathetic modulation as measured from heart rate variability. In addition, the changes in sympathetic modulation and arterial pressure were mostly due to arousals during REM sleep [14]. These data suggest that OSA may alter the physiological response to arousals by exacerbating BP increases, possibly as a result of impaired baroreflex and/or elevated sympathetic activity.…”
Section: Discussionmentioning
confidence: 80%
“…Both abnormal respiratory events and arousals can occur during REM and NREM sleep. Recently, OSA events that occur during REM sleep have been associated with more adverse cardiovascular outcomes than those occurring during NREM, including greater risk of hypertension [14,15]. However, the relationship between arousals during REM and hypertension has not been explored.…”
mentioning
confidence: 99%
“…NBPF patterns are also likely to affect the prognosis of CVD in such patients [ 4 , 5 , 6 , 10 ]. During the sleep stage, apnea during rapid eye movement (REM) sleep was reported to lead to an increase in blood pressure (BP) and sympathetic activity in rats in approximately 2 weeks [ 14 ]. Even in healthy humans, sympathetic activity significantly increased during REM sleep [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive apnea and hypopnea during REM sleep cause more severe hypoxemia, longer apnea duration, and higher activated sympathetic nerve activity than respiratory events during non-rapid eye movement (NREM) sleep [7,8]. It has also been reported that, after only two weeks, apnea during REM sleep resulted in an increase in blood pressure (BP) and sympathetic nerve activity in rats [9]. Even in healthy individuals, sympathetic nerve activity significantly increases during REM sleep [6].…”
Section: Introductionmentioning
confidence: 99%